2023
DOI: 10.1017/s0022149x23000524
|View full text |Cite
|
Sign up to set email alerts
|

Neoskrjabinolepis paradoxa n. sp. from shrews on Sakhalin Island, Russia, with an amended diagnosis of Neoskrjabinolepis Spassky, 1947 (Cestoda: Cyclophyllidea: Hymenolepididae), a key, and a review on geographical distribution of the species

S. A. Kornienko,
T. A. Makarikova,
N. E. Dokuchaev

Abstract: A taxonomic review was performed on cestodes of the genus Neoskrjabinolepis Spassky, 1947 that parasitize different species of Sorex shrews in different regions of the northern Palearctic and in the Nearctic (Alaska, USA). Information on Palearctic Neoskrjabinolepis cestodes published in various articles is summarized. An overview of the geographical distribution of the Neoskrjabinolepis species is also presented. Currently, the genus includes 17 species. In the European part of the Palearctic, four species of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Later, we proved the validity of both species, and a further 15 species have been described within the genus (Kornienko et al, 2006, 2023). Additionally, it has been reported that N. singularis does not occur east of Transbaikalia (Kornienko et al, 2023). Photos of rostellar hooks of N. singularis and their size reported by Sawada and Kobayashi (1993) correspond to N. kedrovensis.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Later, we proved the validity of both species, and a further 15 species have been described within the genus (Kornienko et al, 2006, 2023). Additionally, it has been reported that N. singularis does not occur east of Transbaikalia (Kornienko et al, 2023). Photos of rostellar hooks of N. singularis and their size reported by Sawada and Kobayashi (1993) correspond to N. kedrovensis.…”
Section: Discussionmentioning
confidence: 58%
“…At the time of publication by Sawada and Kobayashi (1993), there was a longstanding discussion about the existence within the genus Neoskrjabinolepis of one or two species having a trans-Palearctic range (i.e., N. singularis and N. schaldybini Spassky, 1947 [Kornienko et al, 2023]). Later, we proved the validity of both species, and a further 15 species have been described within the genus (Kornienko et al, 2006, 2023). Additionally, it has been reported that N. singularis does not occur east of Transbaikalia (Kornienko et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations